(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
The implementation of SMK3RS in Indonesia still shows significant disparities with ideal standards and faces various operational challenges. SMK3RS in various hospitals is not fully aligned with the mandate of Permenkes 66/2016. Non-medical health workers are a work group that has a high occupational safety and health (K3) risk in hospitals, but often have not received optimal training in the Occupational Safety and Health Management System (SMK3). This community service activity aims to improve the knowledge, skills, and attitudes of non-medical health workers in implementing SMK3 procedures in the hospital environment. The activity was carried out in March 2025 at Grandmed Hospital Lubuk Pakam involving 25 non-medical health workers from the cleaning, administration, logistics, and technical units. The activity design used an educational-participatory approach with a pre-post intervention method. Training was conducted through lectures, interactive discussions, demonstrations, and simulations of SMK3 implementation. Evaluation was carried out by comparing the level of knowledge and attitudes of participants before and after the training. The evaluation results showed a significant increase in all indicators. Understanding of basic OHSMS concepts increased from 36% to 88%, the ability to identify occupational hazards and risks increased from 44% to 92%, and understanding of the use of personal protective equipment increased from 40% to 96%. Furthermore, understanding of waste and hazardous materials handling increased from 36% to 88%, knowledge of emergency response procedures increased from 28% to 80%, and positive attitudes toward OHS culture increased from 52% to 96%. Training on the implementation of OHSMS procedures was effective in improving the OHS competency of non-medical healthcare workers and contributed to strengthening OHSMS implementation and creating a safe and healthy hospital work environment.